How Wrong is Paternalism? - Birks, David (Journal of moral philosophy, 2018)
In this paper, I argue against the commonly held view that paternalism is all things considered wrong when it interferes with a person’s autonomy. I begin by noting that the plausibility of this view rests on the assumption that there is a morally relevant difference in the normative reasons concerning an intervention in a person’s self-regarding actions and an intervention in his other-regarding actions. I demonstrate that this assumption cannot be grounded by wellbeing reasons, and that autonomy-based reasons of non-interference also cannot adequately explain the difference. Following this, I propose that the difference in the reasons related to an intervention in a person’s self-regarding actions and an intervention in his other-regarding actions can be explained by the value of holding a person responsible for his choices. Nonetheless, this does not result in paternalistic behavior that interferes with autonomy being all things considered wrong. Instead, I show that the reason to hold a person responsible for a diminution of his wellbeing does not necessarily defeat the wellbeing reasons that count in favor of paternalistic behavior.